Hydrothermal treatments of corn cob and hemicelluloses extraction - Ruzene, Denise S. (2008)
Corn cob samples were treated with water (autohydrolysis reaction) using a liquid to solid ratio of 10:1 w/w. The optimal condition for extraction of hemicelluloses was found at 185ºC for 30 min. This resulted in the release of 9.7% of hemicelluloses (% dry starting material), corresponding to the dissolution of 27.9% of the original hemicellulose. Chemical composition and physico-chemical properties of the samples were elucidated by a combination of sugar analyses and thermal analysis. The results showed that the treatment was effective on the extraction of hemicelluloses from corn cob and that the TGA analysis of xylan from birch wood was found to be initially degraded at about 220 ºC whereas hemicelluloses from corn cob would be degraded at about 225 ºC.